Empowerment and Local Level Conflict Mediation in Indonesia : A Comparative Analysis of Concepts, Measures, and Project Efficacy - Gibson, Christopher (2012)
The notion of empowerment has been more often deductively claimed than carefully defined or inductively assessed by development scholars and practitioners alike. The authors define and assess empowerment through an in-depth examination of the extent to which a large community development project in rural Indonesia empowers participants (especially members of marginalized groups) through building their capacity to manage local conflict. Although the project induces conflict through its deployment of a competitive bidding process, the authors argue that, when well implemented, it can also enable otherwise unequal groups to more peacefully, equitably, and effectively engage one another. Using a mixed methods approach, they compare cases from otherwise similar treatment and control villages to shed light on the chief components of villagers' capacity to manage local conflict. They discuss the interdependencies of two major analytical realms-routines of inter-group collaboration, and sources of countervailing power-and their relation to local conflict processes and outcomes.